Promiscuous coupling between the sulphonylurea receptor and inwardly rectifying potassium channels. - Ammälä, C; Moorhouse, A; Gribble, F; Ashfield, R; Proks, P; Smith, P; Sakura, H; Coles, B; Ashcroft, S; Ashcroft, F (1996)
Sulphonylureas are a class of drugs widely used to treat non-insulin-dependent diabetes mellitus. These drugs act by binding to a sulphonylurea receptor (SUR) in the pancreatic beta-cell membrane which inhibits an ATP-sensitive potassium (K-ATP) channel and thereby stimulates insulin secretion. There has been much debate as to whether SUR and the K-ATP channel are the same or separate proteins, whether SUR confers ATP-sensitivity on an ATP-insensitive pore-forming subunit, and whether sulphonylureas can also modulate other types of K-channel. We show here that SUR itself does not possess intrinsic channel activity but that it endows sulphonylurea sensitivity on several types of inwardly-rectifying K-channels. It does not necessarily confer ATP-sensitivity on these channels.